2021
DOI: 10.1002/acp.3886
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental relationships of executive functions and physiological abilities with game intelligence, game time and injuries in elite soccer players

Abstract: Summary The study examined the (1) interrelation of cognitive‐athletic performance concerning game time and (2) injuries; (3) relation between executive functions and game intelligence. A total of 172 elite soccer players (age: 12–34 years) performed tests assessing multiple‐object‐tracking, working memory capacity (WMC), cognitive flexibility (CF), and inhibition. General and specific‐endurance‐performance, and physical performance (jumps and sprint) were also measured. Game intelligence, time and injuries we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 72 publications
1
12
1
Order By: Relevance
“…Yet, it is also unclear whether those performance improvements appear the other way around as well, i.e., cognitive training improves visual functions. Preliminary evidence suggests that such transfer effects may be limited (Scharfen and Memmert, 2021a). Optimally, future studies investigating those relationships would track behavioral as well as neurophysiological changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, it is also unclear whether those performance improvements appear the other way around as well, i.e., cognitive training improves visual functions. Preliminary evidence suggests that such transfer effects may be limited (Scharfen and Memmert, 2021a). Optimally, future studies investigating those relationships would track behavioral as well as neurophysiological changes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis indicates, that the executive function performance of elite athletes are superior compared to amateur or non-athletes. More precisely, executive functions show relevant associations with several soccer performance related aspects including motor abilities ( Scharfen and Memmert, 2019b ; Reigal et al, 2020a ), game performance ( Sabarit et al, 2020 ; Scharfen and Memmert, 2021b ), psychosocial functioning ( Reigal et al, 2020b ), game intelligence ( Scharfen and Memmert, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In preparation for the study, we identified the n-back task (Kirchner, 1958) as a commonly used task to assess working memory capacities (Conway et al, 2005; see Supplementary Table 1A for justification based on previous studies). Additionally, the n-back task is highly practicable for the implementation in the SoccerBot due to the merely visual representation of the stimuli and the button press response in the computer task, in comparison to other tasks that require verbal responses (e.g., working memory span test, Conway et al, 2005;Scharfen and Memmert, 2021). At this point, it should be noted that other tasks are also used to assess working memory and correlation with soccer performance has been demonstrated (e.g., Backward Visual Memory Span, Huijgen et al, 2015;Corsi-block task, Scharfen and Memmert, 2019;and design fluency, Vestberg et al, 2017).…”
Section: The Present Studymentioning
confidence: 99%
“…Indeed, the empirical evidence demonstrates that elite athletes outperform amateur athletes with respect to some specific cognitive abilities (e.g., executive functions) [ 1 ], especially those athletes that participate in a team-based sport [ 2 ]. In this context, there is also growing evidence that suggests that well-developed cognitive abilities are, among other factors, crucial for success in team sports such as soccer [ 3 , 4 , 5 , 6 , 7 ] or basketball [ 8 , 9 , 10 ]. For instance, Mangine et al (2014) examined the relationship between basketball-specific performance parameters (e.g., assist, steal, turnover) and visual tracking speed (VTS) and reaction time (RT), according to different playing positions (e.g., forward or center), and observed that VTS was related to the performance level of many basketball-specific skills, such as passing or shooting [ 11 ].…”
Section: Introductionmentioning
confidence: 99%